Flood risk governance: Establishing collaborative mechanism for integrated approach - Ishiwatari, Mikio (Progress in Disaster Science, 2019)
It is widely recognized that an integrated approach is needed to reduce flood risks. Many countries are introducing adaptive and integrated systems of risk management in addition to conventional structural and engineering solutions. This paper aims at proposing approach of strengthening a flood risk governance, in particular, collaborative mechanism. The integrated approach involves a wide range of stakeholders of central and local governments, private sector, academia, local communities engaging in various sectors, such as water resources management, agriculture, forestry, housing, and urban planning. However, establishing a collaborative mechanism among these stakeholders is a challenge. The paper reviews recent studies in flood risk governance and examines practices in Japan. It was found that there is no one-fit-all model in flood risk governance. Local bodies on site, trust with stakeholders, and usage of local knowledge are key in strengthening collaborative mechanism.